(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Autism is a pervasive developmental disorder defined by the presence of abnormal and impaired development manifested before the third year of life with a specific type of pathological functioning in all three areas of social interactions, communication and by repetitive behaviour (WHO, 2018). The starting point of this study is whether and to what extent the intensive treatment affects the condition of each child with an autism spectrum disorder. The results from the research demonstrate the existence of a significant improvement of the condition of children with autism spectrum disorder in intensive treatment during the assessment after a certain period of time.